Diffusion Of Innovations Theory, Principles, And Practice - and Dearing, James W.; Cox, Jeffrey G. (Health Affairs, 2018)
Aspects of the research and practice paradigm known as the diffusion of innovations are applicable to the complex context of health care, for both explanatory and interventionist purposes. This article answers the question, “What is diffusion?” by identifying the parameters of diffusion processes: what they are, how they operate, and why worthy innovations in health care do not spread more rapidly. We clarify how the diffusion of innovations is related to processes of dissemination and implementation, sustainability, improvement activity, and scale-up, and we suggest the diffusion principles that can be readily used in the design of interventions.